2013
DOI: 10.4304/jltr.4.6.1160-1166
|View full text |Cite
|
Sign up to set email alerts
|

Arab Practicum Guides Code-switch to Hebrew: Attitudes, Factors and Reasons

Abstract: This study tries to investigate the code-switching behavior of Arabic native speakers who live in Israel. Another objective of this study is to reveal the participants' attitude towards this behavior and the reasons and factors that lead to code-switching. The research tools are audiotape recording and an interview with the participants. 12 respondents participated in this study; their age ranges between 25 and 60. The findings show that the participants' attitude towards code-switching behavior is neutral. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Masrahi (2016) states that teachers and students commonly use MT in Saudi EFL college classrooms and that this is a strategy employed by bilingual teachers to facilitate the educational process. In addition, conversing in the MT can also help teachers explain delicate lexical items, effortlessly clarify meanings, and provide more linguistic input to young students simultaneously learning two languages (Canale, 1983;Brown, 2001;Murad, 2013). Thus, MT is considered a facilitating tool in the English classroom for beginners (Al-Nofaie, 2010;Al-Katheery, 2014;Adil, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Masrahi (2016) states that teachers and students commonly use MT in Saudi EFL college classrooms and that this is a strategy employed by bilingual teachers to facilitate the educational process. In addition, conversing in the MT can also help teachers explain delicate lexical items, effortlessly clarify meanings, and provide more linguistic input to young students simultaneously learning two languages (Canale, 1983;Brown, 2001;Murad, 2013). Thus, MT is considered a facilitating tool in the English classroom for beginners (Al-Nofaie, 2010;Al-Katheery, 2014;Adil, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Hebrew, women code switch to Hebrew unconsciously and unknowingly. Murad (2013) also explains that the use of Hebrew is highly used by the villagers who are in huge contact in business with the Jews. In this research, it's found that most 1948 students have worked at least 1 year in different places as shops, malls, restaurants…etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Others like Murad (2013) argue that 1948 Palestinians don't code switch for prestige; in fact, it's a relative and a personal issue that can only be analysed and tested through real-life situations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…His findings revealed that these students do code-switch between the two languages. Murad (2013) found that Arab guides (instructors) tend to code-switch to Hebrew while teaching in the occupied territory due to the technical and scientific nature of the terms and for the sake of ease. Badr (2003) found that French, Italian and Russian residents in Northern Jordan code-switch to Arabic while communicating in English or French especially when the topic dealt with greetings, local festivals or religious occasions.…”
Section: Related Studies On Arabic and English Csmentioning
confidence: 99%